Functionalized magnetic fiber cloth and preparation method thereof
By modifying the flexible fiber cloth with amino and carboxyl surfaces, and combining amino-modified magnetic nanoparticles and chemically deposited metals, functionalized magnetic fiber cloth is formed, which solves the problem that it is difficult to introduce functional components in the prior art for fiber modification, and achieves high performance and diversified application of the fiber cloth.
Patent Information
- Application Number
- CN202411915000.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-11
AI Technical Summary
The prior art is difficult to introduce functional components without damaging the mechanical strength of the fibers when modifying fibers, resulting in the need for diversified fiber cloths being difficult to meet.
The flexible fiber cloth is subjected to amino and carboxy surface modification treatment, and the amino-modified magnetic nanoparticles are combined, and metal or metal compounds are introduced through chemical deposition to form a functionalized magnetic fiber cloth.
It realizes the high density and high strength of fiber cloth, and has good magnetic, conductive and antibacterial properties, and is suitable for electromagnetic shielding, self-cleaning and light absorption response.
Smart Images

Figure SMS_1 
Figure HDA0005206627830000011 
Figure HDA0005206627830000012
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of textiles, and in particular to a functionalized magnetic fiber cloth and a preparation method thereof. Background Art
[0002] Carbon fiber, polyester fiber, and polyamide fiber have good mechanical strength, and their unique chemical structure makes them excellent in corrosion resistance. However, these fibers have a small number of surface active groups, which makes them difficult to modify functional materials and requires additional surface treatment processes when preparing textiles. Currently, there are three main methods for modifying chemically inert fibers: coating modification, oxidation modification, and grafting modification.
[0003] The coating modification method uses physical methods such as spraying or dipping to coat the resin material on the surface of the inert fiber to form a transition layer. The active functional groups contained in the transition layer can be used as chemical active sites to improve the surface modification ability. The fiber can also be directly modified using a slurry containing functional materials. Chinese patent application CN201810425566 uses a method of separating mixed slurries by magnetic deposition to attach graphene / ferrite materials to a fabric carrier. After placing multiple layers of prepreg and bonding them with adhesive films on both sides of the fabric, a sandwich material with electromagnetic shielding performance can be obtained. Chinese patent application CN202010483825 successively soaked the fiber in a water dispersion of multi-walled nanotubes, polyvinylidene fluoride of ferric oxide and dimethylformamide dispersions, and successfully prepared an electromagnetic shielding hydrophobic fabric. When using physical methods for treatment, the degree of dispersion of functional materials in the slurry has a great influence on the uniformity of modification. During the treatment process, the modification effects of the fiber at the staggered sites and the non-staggered sites are prone to differences, which makes the performance of the functional fabric at different points different, and the product quality fluctuates greatly.
[0004] The oxidation modification method corrodes and oxidizes the fiber, introduces active groups on its surface, and at the same time increases its surface roughness and specific surface area, changes the physical and chemical properties to improve the affinity between the fiber and the functional material; common methods include plasma treatment, oxidation treatment, and electrochemical oxidation for conductive carbon fibers. Affected by the modification methods, the tensile strength of the carbon fiber may be weakened. Chinese patent application CN202210140883 uses hydrogen peroxide and concentrated sulfuric acid to activate and etch carbon fiber. The surface roughness is significantly improved, which can provide active sites for titanium dioxide loading. However, this method uses highly corrosive and oxidizing chemical reagents, which increases the equipment requirements and the risk factor of production. At the same time, it is difficult to control the degree of etching of the carbon fiber, which reduces the structural strength of the carbon fiber. The Chinese patent with publication number CN201910122368 has designed a new activation solution formula, whose main ingredients are dispersant, sodium citrate, nickel salt and borohydride, which effectively simplifies the pre-treatment process and improves the stability of the plating solution. After using nickel salt instead of palladium salt, the production cost is significantly reduced. However, the activation ability of the plating solution is limited, resulting in poor uniformity of the coating and uneven thickness.
[0005] The grafting modification method introduces new active groups (carboxyl, hydroxyl, amine, etc.) on the fiber surface through surface chemical treatment. When the active groups undergo chemical reactions such as esterification, amidation, and coordination, they play a connecting role, enhance the surface reactivity, and achieve effective bonding between polymers or metal ions and fibers. On the one hand, this method can introduce active groups into inert fibers, and on the other hand, the degree of activation of inert fibers can be controlled, reducing damage to the fiber surface, and the growing polymer increases the specific surface area and roughness of the fiber. Chinese patent application CN201911383063 sequentially modifies polydopamine and polyethyleneimine on carbon fibers to improve the hydrophilicity of hydrophobic fibers. After coating polydopamine on magnetic materials, magnetic fillers are grafted onto carbon fibers through Schiff base reaction to obtain magnetic carbon fibers. After high-temperature carbonization of polydopamine and polyethyleneimine in magnetic carbon fibers, carbon-embedded magnetic fillers can be obtained on composite carbon fibers, which improves the conductivity and stability of composite carbon fibers; however, after carbonization, the surface active functional groups are few, and it is still chemically inert, making it difficult to deposit other composite materials.
[0006] Based on the above situation, there is an urgent need to provide a functionalized fiber material that introduces functional components without damaging the mechanical strength of the fiber to meet the diverse needs of fiber cloth. Summary of the invention
[0007] In view of the above technical problems, the present invention successfully grafts polydopamine and polyethyleneimine onto hydrophobic fibers without damaging the structural strength of the hydrophobic fibers, thereby increasing the hydrophilicity of the fibers; further introduces amino groups, and the abundant hydrophilic groups on the surface of the fiber cloth coordinate with metal ions, and introduces functional materials through chemical deposition to functionally modify the fibers. The resulting fiber fabric has a low density and high strength, and through chemical modification, different functional materials can be combined while retaining its original advantages, so that the composite fiber fabric has different physical and chemical properties, etc. The present invention has far-reaching research value and broad application prospects in the fields of electromagnetic shielding, self-cleaning, light absorption response, etc.
[0008] The first aspect of the present invention provides a functionalized magnetic fiber cloth, the preparation raw materials of which at least include: flexible fiber cloth, magnetic nanoparticles, metal or its compound.
[0009] Preferably, the mass ratio of the flexible fiber cloth, the magnetic nanoparticles, the metal or its compound is (3-10): (0.1-1): (0.5-2); more preferably, it is 5:0.5:1-1.5.
[0010] Preferably, the flexible fiber cloth is subjected to amino surface modification treatment and carboxyl surface modification treatment in sequence.
[0011] Preferably, the magnetic nanoparticles are amino-modified.
[0012] Preferably, the flexible fiber cloth is made of carbon fiber cloth.
[0013] The present invention sequentially subjects the flexible fiber cloth to amino surface modification treatment and carboxyl surface modification treatment, then combines it with amino-modified magnetic nanoparticles, and then metal-modifies the flexible fiber cloth with metal or its compound to obtain functionalized magnetic fiber cloth.
[0014] The amino surface modification treatment step of the flexible fiber cloth comprises: using dopamine (DA) and polyethyleneimine (PEI) to carry out oxidative polymerization reaction on the surface of the flexible fiber cloth to obtain the flexible fiber cloth with amino surface modification.
[0015] The carboxyl surface modification treatment step of the flexible fiber cloth comprises: using a carbonyl acid compound to contact and react with the flexible fiber cloth with surface amino groups modified to obtain the flexible fiber cloth with surface carboxyl groups modified.
[0016] The amino modification treatment step of the magnetic nanoparticles comprises: modifying the magnetic nanoparticles with polyethyleneimine, then mixing with dopamine, and performing oxidative polymerization to obtain the surface amino-modified magnetic nanoparticles.
[0017] The magnetic nanoparticles are a combination of one or more of Fe3O4, Co3O4, iron-cobalt alloy, and nickel-iron alloy;
[0018] More preferably, the magnetic nanoparticles are Fe3O4.
[0019] The second aspect of the present invention provides a process for preparing a functionalized magnetic fiber cloth, the preparation steps comprising:
[0020] S1. The flexible fiber cloth is sequentially subjected to amino surface modification treatment and carboxyl surface modification treatment;
[0021] S2. Preparation of amino-modified magnetic nanoparticles;
[0022] S3. activating the flexible fiber cloth treated in step S1, and then allowing the flexible fiber cloth to contact and react with the amino-surface-modified magnetic nanoparticles to obtain a magnetic fiber cloth;
[0023] S4. The magnetic fiber cloth is modified with a metal or a compound thereof to obtain a functionalized magnetic fiber cloth product.
[0024] Preferably, the S1 step comprises:
[0025] S1.1 Amino surface modification treatment: The flexible fiber is placed in a Tris (tris(hydroxymethylaminomethane) buffer solution) buffer solution, and a Tris buffer solution containing DA and PEI is added under heating conditions. After stirring until adsorption equilibrium is reached, a Tris buffer solution containing an oxidant is added and stirred for reaction. After the reaction is completed, the fiber is washed and dried to obtain a flexible fiber cloth with surface amino modification.
[0026] S1.2 Carboxyl surface modification treatment: The flexible fiber with surface amino modified is placed in Tris buffer, and Tris buffer containing carbonyl acid compound is added under heating condition, and stirred for reaction; after the reaction is completed, it is washed and dried to obtain a flexible fiber cloth with surface carboxyl modified.
[0027] Preferably, the oxidant includes a combination of one or more of hydrogen peroxide, persulfate, periodate, and hypochlorite; more preferably, the oxidant includes periodate.
[0028] Preferably, the carbonyl acid compound includes one or more combinations of glyoxylic acid, pyruvic acid, and aldehyde-containing aromatic carboxylic acid compounds.
[0029] The aldehyde-containing aromatic carboxylic acid compounds can be exemplified by aldehyde benzoic acid compounds, aldehyde phenylacetic acid compounds, and the like.
[0030] More preferably, the carbonyl acid compound comprises glyoxylic acid.
[0031] Preferably, the mass ratio of DA to PEI in step S1.1 is 1:(0.5-2); more preferably 1:1.
[0032] Preferably, the reaction temperature in step S1.1 is 30-90°C and the reaction time is 1-6h; more preferably, the reaction is carried out at 65°C for 4h.
[0033] Preferably, in step S1.2, the reaction temperature is 30-60° C. and the reaction time is 1-4 h.
[0034] The present invention utilizes the excellent self-polymerization ability and strong adhesion of dopamine to oxidatively polymerize on the surface of the fiber cloth, and simultaneously, with the participation of polyethyleneimine, oxidative copolymerization reaction with dopamine is carried out to construct a uniform transition layer rich in amino groups on the surface of the hydrophobic fiber layer, thereby effectively improving the surface activity and roughness of the fiber cloth, improving the chemical bonding ability of the fiber cloth, and improving the overall performance of the composite material.
[0035] Furthermore, the present invention introduces a carbonyl acid compound to carry out a Schiff base reaction, which can completely convert the amino groups on the surface of the fiber cloth into carboxyl groups and activate them, and then couple the amino-modified Fe3O4 nanoparticles with the activated carboxyl groups, so that the Fe3O4 nanoparticles can be evenly loaded and coated on the fiber cloth. After investigation, it was found that when the dopamine-modified fiber cloth was directly mixed with the dopamine-modified Fe3O4 nanoparticles, although a small amount of dopamine on the surface of the fiber cloth would polymerize with each other, the steric hindrance effect would significantly weaken the bonding strength of different dopamine interfaces due to the polymerization and the π-π stacking between the benzene rings having a certain directionality. The present invention is designed to activate the fiber cloth first with a straight-chain carbonyl acid, which effectively extends the arm span of the dopamine surface, reduces the steric hindrance, and enhances the bonding ability of the fiber cloth and the Fe3O4 nanoparticles.
[0036] Preferably, before the step S1 is performed, the flexible fiber cloth is first cleaned; specifically, the flexible fiber cloth is placed in a detergent and washed several times to remove oil stains and impurities on the surface of the flexible fiber cloth, and a clean flexible fiber cloth is obtained after washing and drying.
[0037] The detergent is not particularly limited and can be any surfactant commonly used in the art as long as it can achieve the cleaning purpose; for example, sodium lauryl sulfate, sodium alkylbenzene sulfonate, fatty alcohol sulfate, fatty alcohol ether sulfate, alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, etc.
[0038] Preferably, the S2 step comprises: mixing an aqueous solution containing iron salt and ferrous salt with a PEI aqueous solution, adding an alkali solution under stirring conditions, continuing stirring until the reaction is completed, and obtaining PEI-modified magnetic nanoparticles after washing; placing the PEI-modified magnetic nanoparticles in a Tris buffer, heating and ultrasonically stirring, and then adding a Tris buffer containing DA and stirring for reaction; washing and drying after the reaction is completed to obtain amino-modified magnetic nanoparticles.
[0039] Preferably, the S3 step comprises: placing the flexible fiber after amino surface modification treatment and carboxyl surface modification treatment in a weakly acidic buffer, adding Tris buffer containing a carboxyl activator for activation reaction, washing the flexible fiber cloth after activation, and then placing it in a weakly acidic buffer, adding amino-modified magnetic nanoparticles for reaction, washing and drying after the reaction is completed to obtain a magnetic fiber cloth.
[0040] Preferably, the carboxyl activator includes at least one of 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and N-hydroxysuccinimide (NHS).
[0041] Preferably, the activation reaction temperature is 30-60° C., and the activation reaction time is 0.5-4 h.
[0042] Preferably, the S4 step includes: placing the metal or its compound in water and adding ammonia water to obtain a complex solution; arranging the magnetic fiber in the complex solution, adding a treatment agent under heating conditions to perform a precipitation reaction, washing and drying after the reaction is completed, and obtaining a functionalized magnetic fiber cloth.
[0043] The present invention modifies flexible fiber cloth and magnetic nanoparticles respectively by dopamine and polyethyleneimine under conditions of oxidative polymerization, and then utilizes Schiff base reaction to convert amino-modified fiber cloth into carboxyl-modified fiber cloth, and couples the fiber cloth after carboxyl activation with amino-modified magnetic nanoparticles to deposit magnetic nanoparticles on the fiber cloth, and finally deposits metal or metal compound on the magnetic fiber cloth by chemical deposition to obtain a composite fiber fabric with good electrical conductivity, magnetism and light absorption.
[0044] Preferably, the metal or its compound includes one or more combinations of silver, copper, nickel, iron and their oxides or soluble compounds.
[0045] Preferably, the treating agent comprises a reducing agent or a precipitating agent.
[0046] More preferably, the reducing agent includes a combination of one or more of glucose, ascorbic acid, hydroxylamine hydrochloride, hydrazine hydrochloride, and hypophosphite; further preferably, the reducing agent includes at least one of glucose and hydrazine hydrochloride.
[0047] Preferably, the precipitant includes one or more of hydrochloric acid, nitric acid, and sulfide;
[0048] The sulfide can be exemplified by one or more combinations of sulfuric acid, thiosulfate, and thioacetamide.
[0049] Preferably, the precipitation reaction temperature is 40-90° C., and the precipitation reaction time is 1-6 h.
[0050] Preferably, the pH of the Tris buffer is 7.5-9.0.
[0051] The weakly acidic buffer may be exemplified by MES (2-morpholineethanesulfonic acid) buffer, MOPS (3-morpholinepropanesulfonic acid) buffer, HEPES (4-hydroxyethylpiperazineethanesulfonic acid) buffer, Tricine (N-tris(hydroxymethyl)methylglycine) buffer, and the like.
[0052] Preferably, the weakly acidic buffer is a MES buffer; more preferably, the pH of the MES buffer is 5.8-7.0.
[0053] Beneficial effects:
[0054] The present invention provides a functionalized magnetic fiber cloth and a preparation method thereof, which have the following advantages:
[0055] (1) The flexible fiber cloth provided by the present invention is subjected to amino surface modification treatment and carboxyl surface modification treatment in sequence, and then combined with the amino-modified magnetic nanoparticles, and then the flexible fiber cloth is subjected to metal modification by the metal or its compound to obtain a functionalized magnetic fiber cloth; with the help of this design concept, the functionalized design of the fiber cloth can be realized, and the target functionalized material can be flexibly compounded according to the use requirements to improve the performance of the fiber cloth.
[0056] (2) The present invention performs surface modification on the fiber cloth, preferably by amino-modifying the fiber cloth with dopamine or polyethyleneimine, and then adding a carbonyl acid compound to effectively combine with the amino-modified fiber cloth, thereby constructing a uniform transition layer rich in amino groups on the surface of the flexible fiber cloth, providing an active site basis for the combination of the fiber cloth and subsequent functional substances.
[0057] (3) The present invention generates Fe3O4 nanoparticles with good magnetic properties by using ferric ions and ferrous ions in an alkaline environment in the presence of polyethyleneimine; the surface modification of polyethyleneimine is used to inhibit the agglomeration of the nanoparticles, thereby improving the dispersibility of the magnetic nanoparticles in the system, and at the same time, the surface of the nanoparticles is modified with amino groups to provide anchor points for the subsequent coating of polydopamine, thereby further improving the integrity of the surface coating; at the same time, the complete coating layer can also inhibit the oxidation of the Fe3O4 nanoparticles, thereby extending the service life of the functionalized magnetic fiber cloth.
[0058] (4) The surface of the magnetic fiber cloth of the present invention has a large number of carboxyl groups. Compared with the amino groups adjacent to the electron-withdrawing groups, -COO - The group can provide more lone pairs of electrons and has a stronger coordination effect on silver, copper, nickel, iron, etc. The resulting magnetic fiber cloth provides a good chemical deposition site for chemical plating of a variety of metals or metal compounds. Compared with traditional palladium-assisted metal or metal compound deposition, the cost is lower and the performance of the fiber cloth is superior.
[0059] (5) The fiber cloth obtained by the present invention effectively introduces functional materials, effectively combines magnetic nanoparticles and metal materials, and has a good loading effect as shown in microscopic characters, which gives the fiber cloth better magnetic properties. At the same time, the fiber cloth has excellent electrical conductivity and antibacterial properties, and can be well applied in electromagnetic shielding, self-cleaning, light absorption response and other fields.
[0060] (6) The reaction of the present invention is simple and controllable, and compared with the traditional activation method, it is low-cost and does not damage the fiber body. At the same time, the preparation method has good universality and can be flexibly applied to various fiber cloths. Compared with the fiber cloth obtained by modification methods such as coating, it is softer and has a better user experience. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 XRD patterns of the functionalized magnetic fiber cloths of Examples 1-2 and Comparative Examples 1-2 (the gray solid line is Example 1, the red solid line is Example 2, the blue solid line is Comparative Example 1, and the green solid line is Comparative Example 2);
[0062] Figure 2 . Magnetic test diagram of the functionalized magnetic fiber of Example 1-2 and Comparative Example 1-2 (from left to right: Example 1, Example 2, Comparative Example 1, Comparative Example 2);
[0063] Figure 3 . SEM images of the functionalized magnetic fiber cloth of Examples 1-2 and Comparative Examples 1-2 (upper left: Example 1, upper right: Example 2, lower left: Comparative Example 1, lower right: Comparative Example 2);
[0064] Figure 4 Antibacterial test results of the functionalized magnetic fiber cloth of Examples 1-2 and Comparative Examples 1-2 at room temperature and in the dark (upper left: Example 1, upper right: Comparative Example 1, lower left: Example 2, lower right: Comparative Example 2); Figure 5 . Antibacterial test results of the functionalized magnetic fiber cloth of Examples 1-2 and Comparative Examples 1-2 at room temperature and light (upper left: Example 1, upper right: Comparative Example 1, lower left: Example 2, lower right: Comparative Example 2). DETAILED DESCRIPTION
[0065] The material of the flexible fiber cloth used in the present invention is carbon fiber cloth. The reagents used can be purchased from McLean and Aladdin Xilong Chemical Reagent Factory.
[0066] Note: Unless otherwise specified, the solvents of the solutions involved in the present invention are all water; and the raw materials used are all commercially available.
[0067] Example
[0068] Example 1
[0069] This embodiment provides a functionalized magnetic fiber cloth and a preparation method thereof.
[0070] The raw materials for preparing the functionalized magnetic fiber cloth include: flexible fiber cloth, magnetic nanoparticles, and metal compounds.
[0071] The preparation steps of the functionalized magnetic fiber cloth include:
[0072] Step 1: Immerse the flexible fiber cloth in detergent and wash it 3 times at room temperature to remove the oil stains on the surface of the flexible fiber cloth. Then take out the flexible fiber cloth and wash it 3 times with deionized water, and dry it in a 55°C oven to obtain a clean flexible fiber cloth.
[0073] Step 2: Take 5g of clean flexible fiber cloth and add it to a flask containing 440mL Tris buffer (pH=8.5), heat it in a 65℃ water bath and stir it rapidly, add 20mL of Tris buffer solution containing 1.25g DA and 20mL of Tris buffer solution containing 1.25g PEI to the flask in turn, stir for 0.5h to reach adsorption equilibrium, then add 20mL of Tris buffer containing 1.25g oxidant (NaIO4) to the flask, carry out oxidative polymerization reaction at 65℃, stir the reaction for 4h and terminate the reaction, then take out the flexible fiber cloth, wash it with deionized water 3 times and dry it in a 55℃ oven to obtain a flexible fiber cloth with surface amino modification.
[0074] Step 3: Take 5 g of the flexible fiber cloth with surface amino modification and add it to a flask containing 450 mL of Tris buffer (pH = 8.5), heat it in a 55°C water bath and stir it rapidly, add 50 mL of Tris buffer containing 1.25 g of glyoxylic acid to the flask for Schiff base reaction, continue stirring for 3 hours to terminate the reaction, take out the flexible fiber cloth and rinse it with deionized water 3 times, place it in a 55°C oven to dry, and obtain a flexible fiber cloth with surface carboxyl modification.
[0075] Step 4: Place 100 mL of an aqueous solution containing 0.7 g FeCl3 and 0.43 g FeCl2·4H2O in a flask, heat to 60°C in a water bath, turn on the ultrasonic device and keep stirring rapidly, introduce nitrogen to deoxygenate, add 20 mL of an aqueous solution containing 0.1 g PEI to the flask, continue stirring for 20 min, then drop 30 mL of an aqueous solution containing 1.5 g NaOH into the flask, continue stirring for 2 h to terminate the reaction, wash the product with deionized water 5 times, and obtain PEI-modified Fe3O4 nanoparticles. Transfer 0.5 g of PEI-modified Fe3O4 nanoparticles to a flask containing 40 mL of Tris buffer, heat to 30°C in a water bath, turn on the ultrasonic device and stir rapidly for 20 min, then add 10 mL of Tris buffer containing 0.1 g DA to the flask, continue stirring for 16 h to terminate the reaction, wash the product with deionized water 5 times, and obtain surface amino-modified Fe3O4 nanoparticles.
[0076] Step 5: Take 5 g of the flexible fiber cloth with surface carboxyl modified, add 100 mL of MES buffer solution (pH = 6.0) containing 5 g of EDC and 100 mL of MES buffer solution (pH = 6.0) containing 5 g of NHS into the flask in sequence, stir for 1 hour to terminate the reaction, take out the flexible fiber cloth and rinse it twice with MES buffer, then add the flexible fiber cloth into a 150 mL flask filled with MES buffer (pH = 6.0), add 0.5 g of Fe3O4 nanoparticles modified with surface amino groups into the flask, quickly stir for 2 hours to terminate the reaction, then take out the flexible fiber cloth and rinse it three times with deionized water, place it in a 55°C oven to dry, and obtain the magnetic fiber cloth.
[0077] Step 6: Take 1.5g AgNO3 and dissolve it in 100mL deionized water, and slowly drip 15ml 25wt% ammonia water until the precipitate disappears completely, to prepare Ag ammonia solution (i.e., complex solution); take 5g magnetic fiber cloth and add it to a flask containing 115mL silver ammonia solution, heat it to 60℃ in a water bath and stir it rapidly for 0.5h, after reaching adsorption equilibrium, add 35mL of aqueous solution containing 1g glucose drop by drop to the complex solution, continue stirring for 2h after the reducing agent is completely dripped, and end the reaction. Then take out the magnetic fiber cloth and wash it with deionized water 3 times, and dry it in a 55℃ oven to obtain Ag-modified functionalized magnetic fiber cloth.
[0078] Example 2
[0079] This embodiment provides a functional magnetic fiber cloth and a preparation method thereof. The specific implementation method is the same as that of Embodiment 1, except that the difference lies in step six; specifically:
[0080] Step 6: Take 1.3g CuCl2·H2O and dissolve it in 100mL deionized water, and slowly drip 15ml 25% ammonia water until the precipitation disappears completely, to prepare a copper ammonia solution (i.e., complex solution); take 5g magnetic fiber cloth and add it to a flask containing 115mL copper ammonia solution, heat it to 60℃ in a water bath and stir it rapidly for 0.5h. After reaching adsorption equilibrium, add 35mL of an aqueous solution containing 0.3g hydrazine hydrochloride dropwise to the complex solution. After the reducing agent is completely dripped, continue stirring for 2h to terminate the reaction. Then take out the magnetic fiber cloth and wash it with deionized water 3 times, and dry it in a 55℃ oven to obtain Cu-modified functional magnetic fiber cloth.
[0081] Comparative Example 1
[0082] This comparative example provides a functionalized magnetic fiber cloth and a preparation method thereof.
[0083] The raw materials for preparing the functionalized magnetic fiber cloth include: flexible fiber cloth, magnetic nanoparticles, and metal compounds.
[0084] The preparation steps of the functionalized magnetic fiber cloth include:
[0085] Step 1: Immerse the flexible fiber cloth in detergent and wash it 3 times at room temperature to remove the oil stains on the surface of the flexible fiber cloth. Then take out the flexible fiber cloth and wash it 3 times with deionized water, and dry it in a 55°C oven to obtain a clean flexible fiber cloth.
[0086] Step 2: Take 5g of clean flexible fiber cloth and add it to a flask containing 440mL Tris buffer (pH=8.5), heat it in a 65℃ water bath and stir it rapidly, add 20ml of Tris buffer solution containing 1.25g DA and 1.25g PEI to the flask in turn, stir for 0.5h to reach adsorption equilibrium, then add 20mL of Tris buffer containing 1.25g oxidant (NaIO4) to the flask, carry out oxidative polymerization reaction at 65℃, stir the reaction for 4h and terminate the reaction, then take out the flexible fiber cloth, wash it with deionized water 3 times and dry it in a 55℃ oven to obtain a flexible fiber cloth with surface amino modification.
[0087] Step 3: Transfer 5 g of the surface amino-modified flexible fiber cloth and 120 mL of an aqueous solution containing 0.7 g of FeCl3 and 0.43 g of FeCl2·4H2O into a flask, heat it in a water bath to 60°C, turn on the ultrasonic device and maintain rapid stirring, introduce nitrogen to deoxygenate, continue stirring for 20 min, then drop 30 mL of an aqueous solution containing 1.5 g of NaOH into the flask, continue stirring for 2 h to terminate the reaction; take out the flexible fiber cloth and rinse it with deionized water three times, place it in a 55°C oven to dry, and obtain a magnetic fiber cloth.
[0088] Step 4: Take 1.5g AgNO3 and dissolve it in 100mL deionized water, and slowly drip 15ml 25% ammonia water until the precipitation disappears completely, to prepare Ag ammonia solution (i.e., complex solution); take 5g magnetic fiber cloth and add it to a flask containing 115mL Ag ammonia solution, heat it to 60℃ in a water bath and stir it rapidly for 0.5h, after reaching adsorption equilibrium, add 35mL of aqueous solution containing 1g glucose drop by drop into the complex solution, continue stirring for 2h after the reducing agent is completely dripped, and end the reaction. Then take out the magnetic fiber cloth and wash it with deionized water 3 times, and dry it in a 55℃ oven to obtain Ag-modified functional magnetic fiber cloth.
[0089] Comparative Example 2
[0090] This comparative example provides a functionalized magnetic fiber cloth and a preparation method thereof.
[0091] The raw materials for preparing the functionalized magnetic fiber cloth include: flexible fiber cloth, magnetic nanoparticles and metal compounds.
[0092] The preparation steps of the functionalized magnetic fiber cloth include:
[0093] Step 1: Immerse the flexible fiber cloth in detergent and wash it 3 times at room temperature to remove the oil stains on the surface of the flexible fiber cloth. Then take out the flexible fiber cloth and wash it 3 times with deionized water, and dry it in a 55°C oven to obtain a clean flexible fiber cloth.
[0094] Step 2: Take 5g of clean flexible fiber cloth and add it to a flask containing 440mL Tris buffer (pH=8.5), heat it in a 65℃ water bath and stir it rapidly, add 20ml of Tris buffer solution containing 1.25g DA and 1.25g PEI respectively to the flask, stir for 0.5h to reach adsorption equilibrium, then add 20mL of Tris buffer containing 1.25g oxidant (NaIO4) to the flask, carry out oxidative polymerization reaction at 65℃, stir the reaction for 4h and terminate the reaction, then take out the flexible fiber cloth, wash it with deionized water 3 times and dry it in an oven to obtain a flexible fiber cloth with surface amino modification.
[0095] Step 3: Transfer 5 g of the surface amino-modified flexible fiber cloth and 120 mL of an aqueous solution containing 0.7 g of FeCl3 and 0.43 g of FeCl2·4H2O into a flask, heat it to 60°C in a water bath, turn on the ultrasonic device and maintain rapid stirring, introduce nitrogen to deoxygenate, continue stirring for 20 min, then drop 30 mL of an aqueous solution containing 1.5 g of NaOH into the flask, continue stirring for 2 h to terminate the reaction; take out the flexible fiber cloth and rinse it with deionized water three times, place it in an oven to dry, and obtain a magnetic fiber cloth.
[0096] Step 4: Take 1.3g CuCl2·H2O and dissolve it in 100mL deionized water, and slowly drip 15ml25% ammonia water until the precipitation disappears completely, to prepare a copper ammonia solution (i.e., complex solution); take 5 magnetic fiber cloths and add them to a flask containing 115mL copper ammonia solution, heat it to 60℃ in a water bath and stir it rapidly for 0.5h. After reaching adsorption equilibrium, add 35mL of an aqueous solution containing 0.6g of hydrazine hydrochloride dropwise to the complex solution. After the reducing agent is completely dripped, continue to stir for 2h to terminate the reaction. Then take out the magnetic fiber cloth and wash it with deionized water 3 times, and dry it in an oven to obtain Cu-modified functional magnetic fiber cloth.
[0097] Performance Testing
[0098] 1.XRD analysis
[0099] XRD analysis was performed on the functionalized magnetic fiber cloths obtained in Example 1-2 and Comparative Example 1-2. The results are shown in Figure 1 .
[0100] like Figure 1 As shown, the XRD diffraction peaks of the fiber cloths of Example 1-2 and Comparative Example 1-2 show a broad peak at about 2θ=26.5°, which is a standard diffraction peak of carbon fiber.
[0101] The XRD diffraction peaks of Example 1 and Comparative Example 1 appear at 2θ=38.12°, 44.28°, 64.43°, and 77.47°, corresponding to the (1,1,1), (2,0,0), (2,2,0), and (3,1,1) crystal planes in the Ag standard card PDF#04-0783, respectively, indicating that the functionalized magnetic fiber cloth of Example 1 and Comparative Example 1 successfully loaded Ag.
[0102] The XRD diffraction peaks of Example 2 and Comparative Example 2 appear at 2θ=43.41°, corresponding to the (1,1,1) crystal planes in the Cu standard card PDF#03-065-9743, respectively, indicating that the functionalized magnetic fiber cloths of sample Example 2 and Comparative Example 2 successfully loaded Cu, but the amount of Cu deposition in Comparative Example 2 was very small; the XRD peak diffraction peaks of Example 2 also appeared at 2θ=36.42°, 42.30°, and 61.34°, corresponding to the (1,1,1), (2,0,0), and (2,2,0) crystal planes in the Cu2O standard card PDF#05-0667, respectively, indicating that the functionalized magnetic fiber cloth of Example 2 successfully loaded Cu2O, reflecting that controlling the amount of reducing agent used in the preparation method of the present invention can change the deposition ratio of elemental Cu and Cu2O to obtain materials with different functionalities.
[0103] 2. Magnetic analysis
[0104] The magnetic analysis of the functionalized magnetic fiber cloths prepared in Example 1-2 and Comparative Example 1-2 was performed. The results are as follows: Figure 2 As shown in the figure, it can be seen that the four fiber cloth samples can be attracted by the magnet, proving that both Example 1-2 and Comparative Example 1-2 have achieved a certain amount of Fe3O4 deposition.
[0105] 3. SEM analysis
[0106] The functionalized magnetic fiber cloths obtained in Example 1-2 and Comparative Example 1-2 were observed by SEM. Figure 3
[0107] like Figure 3 As shown, after loading amino-modified Fe3O4 and Ag, Example 1 has tens of nanometers of Fe3O4 particles and a large number of hundreds of nanometers of Ag particles on the surface, while the proportion of Fe3O4 and Ag modification in Comparative Example 1 is significantly less, and the deposition uniformity is poor. The deposition effects of Example 2 and Comparative Example 2 are similar to those of Example 1 and Comparative Example 1, respectively, indicating that the introduction of carboxyl groups on the surface of the flexible fiber cloth is more conducive to improving the deposition efficiency of amino-modified Fe3O4 and metal materials, and can also improve the deposition uniformity, thereby improving the functional performance of the fiber cloth.
[0108] 4. Conductive performance analysis
[0109] The conductive properties of the functionalized magnetic fiber cloths prepared in Example 1-2 and Comparative Example 1-2 were analyzed using a multimeter. The resistance of the samples within 1 cm was tested multiple times. The average resistance results are shown in Table 1 below.
[0110] Table 1 Resistance of different functionalized fiber cloths (1 cm)
[0111]
[0112] As shown in Table 1, after Ag plating in Example 1 and Comparative Example 1, the resistance of the fiber cloth decreased significantly with the increase of the amount of Ag plating; after Cu plating in Example 2, the resistance value was relatively high due to the presence of Cu2O with a large band gap on the surface and less single Cu, while after depositing the material in Comparative Example 2, the conductivity of the fiber cloth did not change much due to the presence of only a small amount of Fe3O4 and Cu on the surface; if the amount of metal deposition is further increased, the conductivity of the functionalized fiber cloth can be further improved. The functionalized magnetic fiber cloth prepared by the present invention has good conductivity and can be well applied to electromagnetic shielding, photogenerated electron conduction and other fields.
[0113] 5. Antibacterial performance analysis
[0114] The antibacterial performance of the functionalized magnetic fiber cloth prepared in Example 1-2 and Comparative Example 1-2 was analyzed. The test method was as follows: the sample was placed on a plate coated with 100 μL of 1*10 7 cfu / ml of Escherichia coli in a culture dish, and then place the culture dish at room temperature and culture it under dark / natural light conditions for 48 hours. The results are shown in Figure 4 and Figure 5 .
[0115] like Figure 4 As shown, Example 1 and Example 2 successfully loaded nano-Ag and Cu2O with antibacterial properties, respectively. The functionalized magnetic fiber cloth had a certain killing effect on Escherichia coli in the dark, forming a small range of antibacterial circle, while the loading amount of antibacterial material in Comparative Example 1 and Comparative Example 2 was less, and no obvious antibacterial circle was formed.
[0116] Under light conditions, Fe3O4, Ag, Cu2O, and Cu all have the ability to absorb visible light, and the formation of heterojunctions at the contact surface of different materials can significantly increase the number of photoactive particles (particles with some activity or reactivity generated or activated under light irradiation). Figure 4 and Figure 5 It can be seen that the antibacterial circles formed in Examples 1 and 2 are significantly enlarged after illumination, indicating that the functionalized magnetic fiber cloth can produce specific active particles by absorbing light, thereby improving the sterilization ability. Although the radius of the antibacterial circle of Comparative Example 1 has increased slightly, the antibacterial circle is blurred and the antibacterial performance is still poor; Comparative Example 2 has no antibacterial activity at all, because it has less loaded material and fails to produce a sufficient number of active antibacterial particles under illumination. These results show that a functionalized magnetic fiber cloth with excellent antibacterial performance can be obtained by adopting the preferred scheme of the present invention, and the fiber cloth can absorb light to produce specific active particles during the light adjustment interval, further improving the sterilization ability.
Claims
1. A functionalized magnetic fiber cloth, characterized in that: The preparation raw materials at least include: flexible fiber cloth, magnetic nanoparticles, metal or its compound; The flexible fiber cloth is sequentially subjected to amino surface modification treatment and carboxyl surface modification treatment; The magnetic nanoparticles are treated with amino group modification.
2. The functionalized magnetic fiber cloth according to claim 1, characterized in that: The amino surface modification treatment step of the flexible fiber cloth comprises: using dopamine and polyethyleneimine to carry out oxidative polymerization reaction on the surface of the flexible fiber cloth to obtain the flexible fiber cloth with amino surface modification.
3. The functionalized magnetic fiber cloth according to claim 2, characterized in that: The carboxyl surface modification treatment step of the flexible fiber cloth comprises: using a carbonyl acid compound to contact and react with the flexible fiber cloth with surface amino groups modified to obtain the flexible fiber cloth with surface carboxyl groups modified.
4. The functionalized magnetic fiber cloth according to claim 1, characterized in that: The amino modification treatment step of the magnetic nanoparticles comprises: modifying the magnetic nanoparticles with polyethyleneimine, then mixing with dopamine, and performing oxidative polymerization to obtain the surface amino-modified magnetic nanoparticles.
5. The functionalized magnetic fiber cloth according to claim 1, characterized in that: The magnetic nanoparticles are a combination of one or more of Fe3O4, Co3O4, iron-cobalt alloy, and nickel-iron alloy; Preferably, the magnetic nanoparticles are Fe3O4.
6. A method for preparing the functionalized magnetic fiber cloth according to any one of claims 1 to 5, characterized in that: The preparation steps include: S1. The flexible fiber cloth is sequentially subjected to amino surface modification treatment and carboxyl surface modification treatment; S2. Preparation of amino-modified magnetic nanoparticles; S3. activating the flexible fiber cloth treated in step S1, and then allowing the flexible fiber cloth to contact and react with the amino-surface-modified magnetic nanoparticles to obtain a magnetic fiber cloth; S4. The magnetic fiber cloth is modified with a metal or a compound thereof to obtain a functionalized magnetic fiber cloth product.
7. The method for preparing the functionalized magnetic fiber cloth according to claim 6, characterized in that: The S1 step includes: Amino surface modification treatment: the flexible fiber is placed in a Tris buffer, a Tris buffer containing dopamine and polyethyleneimine is added under heating conditions, and after stirring until adsorption equilibrium is reached, a Tris buffer containing an oxidant is added and stirred for reaction; after the reaction is completed, the flexible fiber cloth is washed and dried to obtain a surface-amino-modified flexible fiber cloth; Carboxyl surface modification treatment: The flexible fiber with surface amino modified is placed in Tris buffer, and a Tris buffer containing a carbonyl acid compound is added under heating conditions, and the reaction is stirred; after the reaction is completed, the flexible fiber cloth with surface carboxyl modified is washed and dried to obtain.
8. The method for preparing the functionalized magnetic fiber cloth according to claim 6, characterized in that: The S2 step comprises: mixing an aqueous solution containing iron salt and ferrous salt with an aqueous solution of polyethyleneimine, adding an alkali solution under stirring conditions, continuously stirring until the reaction is completed, and washing to obtain polyethyleneimine-modified magnetic nanoparticles; placing the polyethyleneimine-modified magnetic nanoparticles in a Tris buffer, heating and ultrasonically stirring, then adding a Tris buffer containing dopamine, and stirring for reaction; washing and drying after the reaction is completed to obtain amino-modified magnetic nanoparticles.
9. The method for preparing the functionalized magnetic fiber cloth according to claim 6, characterized in that: The step S3 comprises: placing the flexible fiber treated in the step S1 in a weak acidic buffer, adding a Tris buffer containing a carboxyl activator to perform an activation reaction, placing the flexible fiber in a weak acidic buffer after activation, adding amino-surface-modified magnetic nanoparticles to perform a reaction, and washing and drying after the reaction to obtain a magnetic fiber cloth; The carboxyl activator includes at least one of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide; The temperature of the activation reaction is 30-60° C., and the time of the activation reaction is 0.5-4 h.
10. The method for preparing the functionalized magnetic fiber cloth according to claim 6, characterized in that: The step S4 comprises: placing the metal or its compound in water and adding ammonia water to obtain a complex solution; placing the magnetic fiber in the complex solution, adding a treatment agent under heating conditions to perform a precipitation reaction, and washing and drying after the reaction is completed to obtain a functional magnetic fiber cloth; The temperature of the precipitation reaction is 40-90° C., and the time of the precipitation reaction is 1-6 hours.
Citation Information
Patent Citations
Preparation method of electromagnetic shielding honeycomb core material
CN108724822A
Activator, preparation method and preparation method of carbon fiber composite material
CN109735830A
A modified carbon fiber, its preparation method and its application
CN111116992B
Electromagnetic shielding and hydrophobic functional fabrics with high absorption properties and their preparation methods
CN111535044B
Composite material with reduced titanium dioxide loaded on surface of carbon fiber as well as preparation and application of composite material
CN114974918A
Cited By
Ag / Fe3O4 synergistically modified basalt fiber and PVDF composite material and preparation method thereof
CN121159947A